Jøder i fængsel for 200 år siden - Bendixen, Otto (Rambam. Tidsskrift for jødisk kultur og forskning, 2023)
Records in The Danish National Archives about Jewish prisoners contain information that is not available elsewhere. Jewish prisoners were only a few in the total number of prisoners, but their records hold valuable information. Many Jews were born in foreign countries, and this information was difficult to get at that time. You can also find descriptions of each prisoner, which makes it possible to get an idea of him or her before the invention of the photography. Many Jewish women were imprisoned because of prostitution, and several of the prisoners had children with them in the prison. Most of the sources are available online at https://www. sa.dk/ao-soegesider/da/collection/theme/14.